Nitrate contamination in New Zealand's domestic drinking water with a focus on rural groundwater-sourced self-supplies - Karyne M. Rogers; Diane Bradshaw; Phil Scadden; Conny Tschritter; Stuart Sanderson; Jannine Cooper; Andy Phillips; Jennifer Pannell; Juliane Thern; Steve Abel; Michael K. Joy; Xing Liu; et al. (Science of The Total Environment, 2025)

Adverse impacts of off-road vehicles on coastal dune vegetation are widespread, substantial, and long-lasting: Evidence from a global meta-analysis of sandy beach-dune systems - Thomas A. Schlacher; Michael A. Weston; Shane Orchard; Brendan P. Kelaher; Brooke Maslo; Jenifer E. Dugan; David M. Hubbard; Leonardo Costa; Melanie J. Bishop; Kristal N. Kostoglu; Ben L. Gilby; Christofer J. Henderson; et al. (Estuarine, Coastal and Shelf Science, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Small invertebrates in bivalve-cultivated and unmodified habitats of nearshore ecosystems - Stuart H. Munsch; Julie S. Barber; Jeffery R. Cordell; Peter M. Kiffney; Beth L. Sanderson; Jason D. Toft (Hydrobiologia, 2021)
Many nearshore ecosystems are modified by aquaculture, including bivalve culture to produce food and restore extirpated populations. Small invertebrates in nearshore ecosystems support fundamental ecological processes, but the effects of bivalve culture on invertebrates are incompletely understood. Here, we compared invertebrate assemblages from multiple studies of bivalve-cultivated and unmodified nearshore habitats along the US west coast. In general, unmodified eelgrass and nearby off-bottom culture habitats with eelgrass present were inhabited by a greater abundance, richness, and diversity of epibenthic invertebrates than bottom culture and bare (mud, sand) habitats that both lacked eelgrass. Findings of individual studies suggested: minor differences in epibenthic invertebrate assemblages associated with various aquaculture practices; restoring native oysters to mudflats did not detectably alter epibenthic invertebrate abundances; epibenthic invertebrates were more abundant on shell hash introduced to mudflats than unmodified mudflats; and benthic invertebrates were less abundant, rich, and diverse in habitats cultured on bottom by Manila clams. Considering the range of these patterns, there appears to be potential for coastal communities to restore extirpated bivalve populations or develop bivalve culture practices that meet objectives to grow food while maintaining nearshore ecosystems’ fundamental processes supported by robust invertebrate assemblages.

The checkered history of checkerboard distributions: comment - Jared Diamond; Stuart L. Pimm; James G. Sanderson (Ecology, 2015)

Transcriptomics of coping strategies in free‐swimming Lepeophtheirus salmonis (Copepoda) larvae responding to abiotic stress - Ben J. G. Sutherland; Stuart G. Jantzen; Motoshige Yasuike; Dan S. Sanderson; Ben F. Koop; Simon R. M. Jones (Molecular Ecology, 2012)
The salmon louse Lepeophtheirus salmonis is a marine ectoparasite of wild and farmed salmon in the Northern Hemisphere. Infections of farmed salmon are of economic and ecological concern. Nauplius and copepodid salmon lice larvae are free‐swimming and disperse in the water column until they encounter a host. In this study, we characterized the sublethal stress responses of L. salmonis copepodid larvae by applying a 38K oligonucleotide microarray to profile transcriptomes following 24 h exposures to suboptimal salinity (30–10 parts per thousand ( ‰ )) or temperature (16–4 °C) environments. Hyposalinity exposure resulted in large‐scale gene expression changes relative to those elicited by a thermal gradient. Subsequently, transcriptome responses to a more finely resolved salinity gradient between 30 ‰ and 25 ‰ were profiled. Minimal changes occurred at 29 ‰ or 28 ‰ , a threshold of response was identified at 27 ‰ , and the largest response was at 25 ‰. Differentially expressed genes were clustered by pattern of expression, and clusters were characterized by functional enrichment analysis. Results indicate larval copepods adopt two distinct coping strategies in response to short‐term hyposaline stress: a primary response using molecular chaperones and catabolic processes at 27 ‰ ; and a secondary response up‐regulating ion pumps, transporters, a different suite of chaperones and apoptosis‐related transcripts at 26 ‰ and 25 ‰ . The results further our understanding of the tolerances of L. salmonis copepodids to salinity and temperature gradients and may assist in the development of salmon louse management strategies.

Reciprocal specialization in ecological networks - Lucas N. Joppa; Jordi Bascompte; Jose M. Montoya; Ricard V. Solé; Jim Sanderson; Stuart L. Pimm (Ecology Letters, 2009)
Theories suggest that food webs might consist of groups of species forming ‘blocks’, ‘compartments’ or ‘guilds’. We consider ecological networks – subsets of complete food webs – involving species at adjacent trophic levels. Reciprocal specializations occur when (say) a pollinator (or group of pollinators) specializes on a particular flower species (or group of such species) and vice versa. Such specializations tend to group species into guilds. We characterize the level of reciprocal specialization for both antagonistic interactions – particularly parasitoids and their hosts – and mutualistic ones – such as insects and the flowers that they pollinate. We also examine whether trophic patterns might be ‘palimpsests’– that is, there might be reciprocal specialization within taxonomically related species within a network, but these might be obscured when these relationships are combined. Reciprocal specializations are rare in all these systems when tested against the most conservative null model.